The enhancement criteria of green building implementation for property development in Perak, Malaysia – valuers’ perspective / Roshdi Sabu, Hayroman Ahmad and Lizawati Abdullah - Roshdi, Sabu; Hayroman, Ahmad; Lizawati, Abdullah (2015)
This paper is conducted to assess valuers‘ perspective regarding sluggish performance of Green Building (GB) implementation for property development in Perak, Malaysia. The aim of this paper is to recommend the criteria for enhancement of Green Building implementation for property development in Perak, Malaysia from valuers‘ point of view. The study involved valuers in Perak which were consisting of registered valuers, appraisers, probationary valuers and non-registered or probationary valuers in private and government sector. Most of them were also getting involved in GB experiences for Penang and Selangor. With total population of 176 respondents, a questionnaire survey was conducted involving valuers or appraisers with registered business address in Perak, Malaysia. The data have been analysed using Factor Analysis technique of Statistical Package for Social Sciences. The results revealed consist of several nhancement criteria for Green Building implementation in Perak such as Green Awareness and Knowledge, Green Commitment, Green Collaboration of Construction and Financial Sector, Green Information Database, Green Incentive Schemes, Green Continuous Professional Development Centre, Green Integrated Professional Experts, Green Feedback and Green Return on Investment. Hence, those criteria could be applied for the future of Green Building implementation in the state of Perak where the collaboration between stakeholders and market representatives on green property market through valuers‘ expert opinions will ensure the success of Green Building development can be accomplished.